Combined evaluation of Geriatric nutritional risk index and Neutrophil to lymphocyte ratio for predicting all-cause and cardiovascular mortality in hemodialysis patients. - Jun Wang; Li-Juan Huang; Bei Li; Mei-Chang Xu; Lei Yang; Xu Deng; Xin Li (PLoS ONE, 2023)
Objective Malnutrition, accompanied by an inflammatory profile, is a risk factor for poor prognosis in hemodialysis patients. The purpose of this study was to investigate the predictive value of NLR combined with GNRI for all-cause and cardiovascular mortality in hemodialysis patients. Methods A total of 240 maintenance hemodialysis (MHD) patients in hemodialysis centers were enrolled in this retrospective study. The influencing factors of all-cause death in hemodialysis patients were analyzed by COX regression. The cut-off values of GNRI and NLR for predicting mortality in enrolled MHD patients were 89.01 and 4, respectively. Based on these cut-off values, the patients were divided into four groups: G1: high GNRI (≥ 89.01) + high NLR (≥ 4) group; G2: high GNRI (≥ 89.01) + low NLR (<4) group, G3: low GNRI (< 89.01) + high NLR (≥4) group; G4: low GNRI (< 89.01) + low NLR (<4). Results During the follow-up period (average: 58 months), the all-cause mortality was 20.83%(50/240) and the cardiovascular mortality was 12.08%(29/240). Both NLR and GNRI were independent risk factors for the prognosis of MHD patients (P<0.05). Survival analysis showed that patients with low GNRI had a lower survival rate than those with high GNRI, whereas patients with high NLR had a lower survival rate than those with low NLR. Kaplan-Meier curve for all-cause mortality revealed that compared to G1, G2, and G4, G3 had the lowest survival rate, while G2 had the highest survival rate among all groups (P < 0.05). Kaplan-Meier curve for cardiovascular mortality showed that G3 had lower survival than G1, G2, and G4 (P < 0.001). Conclusions Our study demonstrates that bothGNRI and NLR are associated with all-cause mortality and cardiovascular mortality in MHD patients. Combining these two factorsmay contribute to a prognostic evaluation for MHD patients.